Xuanfei Pingchuan Capsules Ameliorate Autophagy in Human Bronchial Epithelial Cells by Inhibiting p38 Phosphorylation - Xiaoming Xue; Lihong Meng; Hongyu Cai; Yaoqin Sun; Ye Zhang; Hao Li; Yu Kang; Bobo Zhou; Fang Shang; Wei Guan; Li Zhang; Xu Chen; et al. (Frontiers Media S.A., 2021)
Background: This study aimed to investigate the protective effect of Xuanfei Pingchuan Capsules (XFPC) on autophagy and p38 phosphorylation in human bronchial epithelial (HBE) cells induced by cigarette smoke extract (CSE).Methods: HBE cells were divided into five groups: blank, CSE, low XFPC dose (XFPC-L), medium XFPC dose (XFPC-M), and high XFPC dose (XFPC-H). HBE cells were induced by CSE to establish a cell model for chronic obstructive pulmonary disease, and different doses of XFPC medicated serum were used to treat the cells. The Cell Counting Kit-8 was used to detect cell viability. Flow cytometry was used to detect cell apoptosis. Fluorescence microscopy and the expression level of microtubule-associated protein light chain 3 (LC3)-II in immunohistochemical method were used to observe autophagy in cells. Western blot was used to detect the protein expression level of p38, phospho-p38 (p-p38), LC3-I, LC3-II and Beclin 1. Real-time polymerase chain reaction was used to detect the expression of LC3-I, LC3-II and Beclin 1 on mRNA level.Results: Compared with the blank group, the cell viability of the CSE group was significantly decreased, and apoptosis and the level of autophagy in cells were significantly increased. The mRNA and protein expression of LC3-I, LC3-II, Beclin 1 and the protein level of p-p38 were significantly increased in the CSE-HBE cells. Compared to the CSE group, the different doses of XFPC medicated serum increased cell viability, decreased cell apoptosis, and inhibited mRNA and protein expression of LC3-I, LC3-II, Beclin 1 and protein level of p-p38. These results were especially observed in the group XFPC-H. After adding a p38 agonist, the therapeutic effect of XFPC on cell viability and autophagy was suppressed.Conclusion: XFPC significantly increased cell viability in a CSE-induced HBE cell model for chronic obstructive pulmonary disease through inhibiting the level of autophagy mediated by phosphorylation of p38.